MEDIA MASSA DAN DAKWAH - Japaruddin Japaruddin (Institut Agama Islam Negeri Bengkulu, 2014)
The development was accompanied by advances in information technology communication media. As with any communication, Islamic missionary activities in absolute need of media propaganda. Submission of propaganda message of Islam today ideally utilize the media can reach the general public and rigorous, one of the mass communication media that can be used in the Islamic Propagation communication is television media. Television has a diverse audience and almost every time hit viewers, for the propaganda on television today is quite can be calculated.